PENERAPAN SANKSI ADMINISTRASI BAGI PERUSAHAAN PERKEBUNAN YANG MELAKUKAN PELANGGARAN HUKUM DI BIDANG PERKEBUNAN - Hendra Pratikno Manurung; Kartina Pakpahan; Valentin Tania; Reno Aditya Suhendro; Mei Fernando Marpaung (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
The purpose of this research is to regulate the administration of administrative sanctions in the plantation sector, the application of administrative sanctions for plantation companies and the supervision efforts undertaken by the government as an effort to prevent administrative violations in the plantation sector. Using normative juridical research, namely library research. The source of legal materials used is secondary data. Law Number 18 of 2004 concerning plantations states that realizing the prosperity of the community and welfare in a fair manner, one form of processing natural resources is needed in a responsible, planned, integrated and professional manner.